Characteristics and Mechanism of Pb2+ Adsorption From Aqueous Solution Onto Biochar Derived From Microalgae and Chitosan-Modified Microalgae - Liu, Weigang; Li, Kelin; Hu, Xi; Hu, Xinjiang; Zhang, Ruibin; Li, Qi (Frontiers in Environmental Chemistry, 2021)
With the increasingly serious problem of aquatic heavy metal pollution and water eutrophication, using algae to prepare a new a new adsorbent material to remediate heavy metal pollution has recently become a hot topic worldwide. Modified Microalgae biochar and its application in environmental pollution remediation has attracted an increasing amount of attention from researchers. In this study, Two new type of microalgae biochar is developed as adsorbent material using Clostridium and adding chitosan as a modifier at different stages of its preparation. These new microalgae biochar were characterized using BET surface area,Fourier transform infrared spectroscopy(FTIR),scanning electron microscopy(SEM). The adsorption processes of these biochars are well described by a pseudo-second-order kinetic model.The adsorption of Pb2+ by microalgal biochar was dominated by chemical adsorption. After chitosan modification, many amino, cyano, and aromatic ring groups attached to the surface of the microalgal biochar. The adsorption capacity of the chitosan modified biochar for Pb2+ was better than that of the unmodified microalgae biochar. The maximum Pb2+ adsorption capacities of chitosan-biochar(CTS-BC) at acidic conditions (pH=5) were 9.41mg/g;The maximum Pb2+ adsorption capacities of biochar-chitosan(BC-CTS) at alkaline conditions (pH=9) were 9.94mg/g, which were higher than unmodified microalgae biochar at the same conditions.This study demonstrated that adsorbent materials with stronger adsorption capacity for heavy metals can be prepared by adding chitosan during different stages of the microalgae biochar preparation process.